Comparative morphology of the digestive tract of two Neotropical tree frogs (Genus Boana) - Valverde, Bruno S.L. [UNESP]; Fanali, Lara Zácari [UNESP]; Franco-Belussi, Lilian [UNESP]; de Oliveira, Classius [UNESP] (Elsevier, 2019)
The vertebrate digestive system, responsible for providing nutrients for maintaining body homeostasis, consists of two components in anurans: the digestive tract and the accessory glands. The digestive tract includes the oral cavity, pharynx, esophagus, stomach, and small and large intestine, ending in the cloaca. Morphological characteristics of the digestive tract are distinct between anuran species. In this work, we describe the digestive tract of anurans of the genus Boana, establishing a comparison between the other anurans already described in the literature. For this, six adult male specimens of each species, Boana albopunctata and Boana raniceps, were collected. The digestive tracts were removed and processed for the anatomical and histological analyses of their different components. In both species, the esophagus, stomach and intestines had similar anatomo-histological characteristics. However, histological divergences were observed with respect to the presence of pluricellular glands in the esophagus, muscle cells in the submucosa of the esophagus and intestines, and the type of esophageal epithelium, compared to other anurans. These findings corroborate the interspecific differences between anurans and provide knowledge for future studies aimed at evaluating the digestive system in Neotropical anurans.
Keywords: Anurans; Digestive system; Esophagus; Intestine; Stomach